Determinants of breastfeeding indicators among children less than 24 months of age in Tanzania: a secondary analysis of the 2010 Tanzania Demographic and Health Survey - Victor, Rose (BMJ Publishing Group, 2013)
OBJECTIVE: To examine the prevalence of key WHO breastfeeding indicators and identify determinants of suboptimal breastfeeding practices among children aged less than 24 months in Tanzania. DESIGN, SETTING AND PARTICIPANTS: Secondary analyses of cross-sectional data from the 2010 Tanzania Demographic and Health Survey. The survey used a stratified two-stage cluster sample of 10 312 households from eight geographical zones of Tanzania. The sample consisted of 3112 children aged 0–23 months. MAIN OUTCOME MEASURES: Outcome measures were factors significantly associated with delayed initiation of breastfeeding, non-exclusive breastfeeding and predominant breastfeeding in the first 6 months. RESULTS: Breastfeeding was initiated within the first hour of birth in 46.1% of mothers. In infants aged less than 6 months, the prevalence of exclusive breastfeeding was 49.9% but only 22.9% were exclusively breastfed at 4–5 months. Seventeen per cent of infants, less than 6 months of age, were ‘predominantly breastfed’. At 12–15 months, 94.0% of infants were still breastfed but the proportion decreased to 51.1% at 20–23 months of age. Multivariate analysis revealed that the risk of delayed initiation of breastfeeding within 1 h after birth was significantly higher among young mothers aged <24 years, uneducated and employed mothers from rural areas who delivered by caesarean section and those who delivered at home and were assisted by traditional birth attendants or relatives. The risk factors associated with non-exclusive breastfeeding, during the first 6 months, were lack of professional assistance at birth and residence in urban areas. The risk of predominant breastfeeding was significantly higher among infants from the Zanzibar geographical zone. CONCLUSIONS: Early initiation of breastfeeding and exclusive breastfeeding indicators were unsatisfactory and are below the national targets for Tanzania. To improve breastfeeding practices, national level programmes will be required, but with a focus on the target groups with suboptimal breastfeeding practices.